Accumulation and bioaccessibility of toxic metals in root tubers and soils from gold mining and farming communities in the Ashanti region of Ghana. Issue 2 (1st February 2022) - Darko, Godfred; Adjei, Samuel; Nkansah, Marian Asantewah; Borquaye, Lawrence Sheringham; Boakye, Kwadwo Owusu; Dodd, Matt
ABSTRACT: The presence of metal contaminants in agricultural soils and subsequent uptake by food crops can pose serious human health risk. In this study, we assessed the levels of toxic metals – arsenic, chromium, copper, iron, manganese, nickel, and zinc – in soils and some edible root tuber crops from two gold mining and two non-mining communities in Ghana to evaluate the potential human health risks associated with exposure to these metals. Concentrations of the metals in 154 soil and edible root tuber samples were analyzed using field portable x-ray fluorescence spectrometer prior to confirmation by inductively coupled plasma mass spectrometry. Bioaccessibility of the metals was determined using an in vitro physiologically based extraction technique. Concentrations of the metals were generally higher in the gold mining communities than in the non-mining communities. The contamination indices indicated low to moderate contamination of the soil and food crops. Bioaccessibility for the metals varied from 1.7% (Fe) to 62.3 (Mn). Overall, the risks posed by the metals upon consumption of the tubers were low.